Modeling of the Signal Transmission of a Coaxial Connector With a Degraded Dielectric Layer in a Humid Environment - Wang, Wenjia; Gao, Jinchun; Flowers, George T.; Wang, Ziren; Bi, Lingyu; Bilal, Hafiz M. (IEEE transactions on dielectrics and electrical insulation, 2022)
Radio frequency coaxial connectors are key components in circuits for signal transmission and directly influence the stability of communication systems. It is well known that connectors operating in harsh environments for extended periods are subject to physical degradation, which may lead to deterioration of signal integrity and overall communication quality. However, little work has been done with regard to connector dielectric degradation in humid environments. In this current work, the specific effects of connector dielectric degradation in humid environments on signal transmission are studied by theoretical and experimental analysis. Both a 3-D electromagnetic field model and an equivalent circuit model for connectors before and after degradation are developed in order to evaluate signal reflection and transmission loss. The results of these two models are compared and show good agreement. In addition, based on the material properties of the connector dielectric, the equivalent dielectric layer of a degraded connector is considered to consist of a double-layer dielectric structure composed of polytetrafluoroethylene (PTFE) and a layer of water film. The equivalent dielectric constant and equivalent loss tangent of the double-layer dielectric structure are calculated and analyzed. A corresponding equivalent circuit is developed consisting of an impedance network with resistance and capacitance elements in parallel. Experiment tests are conducted to validate the electromagnetic field model and the circuit model results. The results of this research provide a better understanding of the electrical characteristics of degraded connectors in humid environments and theoretical support for engineering applications.